Soil organic carbon stabilization and associated mineral protection in typical coastal wetlands under different hydrologic conditions - Zhao, Haixiao; Jia, Jia; Zhao, Qingqing; Wang, Jianing; Gao, Yongchao; Huang, Yujie; Chen, Guanhong (Frontiers in Marine Science, 2022)
The soil carbon sequestration largely depends on soil organic carbon (SOC) stability. However, the mechanism of SOC stabilization in coastal wetlands under different hydrologic conditions remains to be clarified. In this study, the effect of mineral protection on SOC stability was investigated in freshwater-flooded Phragmites australis wetlands (FPW), tidal P. australis wetlands (TPW), non-flooded P. australis wetlands (NPW) and tidal Suaeda salsa wetlands (TSW). Two stabilized SOC fractions (Na2S2O8 resistant SOC and H2O2 resistant SOC) and Al/Fe/Si oxides extracted by acid oxalate, dithionite–citrate and pyrophosphate, respectively, were determined in soil samples collected to a depth of 25 cm. The contents of soil Na2S2O8 resistant SOC and H2O2 resistant SOC were not significantly different among the four wetlands (p > 0.05), with the highest mean values occurring in FPW (1.44 ± 0.43 g kg-1) and TPW (1.79 ± 0.40 g kg-1), respectively. The contents of Al/Fe/Si oxides (except for Sip) and the values of mineral phase indicators were significantly lower in NPW than in TPW or FPW (p < 0.05). Linear regressions among Al/Fe/Si oxides, mineral phase indicators, and two stabilized SOC fractions showed that Na2S2O8 resistant SOC and H2O2 resistant SOC were positively and significantly affected by mineral contents (p < 0.05). Additionally, edaphic factors such as soil organic matter, total nitrogen, soil water content, clay and silt contents were identified as important factors influencing the two stabilized SOC fractions.